1967
DOI: 10.1111/j.1432-1033.1967.tb00162.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐Chain and Globin: Intermediates in the Synthesis of Rabbit Hemoglobin

Abstract: The synthesis of hemoglobin by rabbit reticulocytes has been studied by means of pulselabelling and chase experiments. The reticulocyte lysate was fractionated into a top layer and a ribosomal fraction. The top layer was analysed by gel filtration on columns of Sephadex 6-75. At least two intermediates which were formed after short incubations and were chased into hemoglobin were separated by gel filtration. These intermediates have been identified with a chain and globin.a Chain and globin have also been sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1971
1971
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Given that a small pool of free a chains is known to exist in erythroblasts (8,20,40,64,77,93,97), Yu et al (119) hypothesized that the ill effects caused by Ahsp gene disruption might be mitigated by lowering a globin gene dosage. This would reduce or eliminate the pool of free a chains that are unescorted by AHSP, and consequently might lessen the severity of the Ahsp knockout phenotype (119).…”
Section: Role Of Ahsp As a Chaperone During Hemoglobin Productionmentioning
confidence: 99%
“…Given that a small pool of free a chains is known to exist in erythroblasts (8,20,40,64,77,93,97), Yu et al (119) hypothesized that the ill effects caused by Ahsp gene disruption might be mitigated by lowering a globin gene dosage. This would reduce or eliminate the pool of free a chains that are unescorted by AHSP, and consequently might lessen the severity of the Ahsp knockout phenotype (119).…”
Section: Role Of Ahsp As a Chaperone During Hemoglobin Productionmentioning
confidence: 99%
“…Rabbit reticulocytes synthesize essentially equal amounts of the a and chains of hemoglobin (20)(21)(22). The experiments shown in Figs.…”
Section: Discussionmentioning
confidence: 91%
“…It has been suggested that achains assist in the removal of completed f8-chains from polyribosomes (22,23 …”
Section: Methodsmentioning
confidence: 99%
“…Table I lists the patients whose blood was used for the study of P-globin m-RNA translation. Five patients of Italian descent, ages [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] yr, with Cooley's anemia or P-thalassemia major were examined. All had severe anemia and, except for one patient, required blood transfusions at 1-2 month intervals.…”
Section: Methodsmentioning
confidence: 99%